Propuesta de Concresor basado en Relaciones Booleanas - Soriano Méndez, José Jairo; González Melo, Omar Lorenzo; Munar Fontecha, Franck Vladimir; Ramos Acosta, Andrés Augusto (Ingeniería, 2000)
This paper introduces to a new method in the design of fuzzy controllers, looking for as main objective to simplify or to reduce the complexity of the traditional deffuzzifiers without changes on theirs effectiveness, the used way for such an end is to begin of the Boole's logic to arrive to a fuzzy control surface.